2020
DOI: 10.1177/1708538120911302
|View full text |Cite
|
Sign up to set email alerts
|

Our experience regarding patients with headache, vomiting, and urinary retention following endothermal ablation of the greater saphenous vein under spinal anesthesia: Gender type, age interval, and procedural risk factors are important

Abstract: Objectives The endovenous thermal ablation of the greater saphenous vein under spinal anesthesia is still a popular technique. Although this procedure is considered to be fast and simple, side effects such as headaches, vomiting, and urinary retention could occur. These side effects make the recovery period difficult for the patient. The patient’s age, gender, and procedural risk factors such as needle sizes and types are important parameters that affect the occurrence and rate of undesirable outcomes. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 15 publications
(35 reference statements)
3
7
0
Order By: Relevance
“…Younger age and female sex have been reported to be associated with the development of POH in various surgeries ( 8 , 9 , 11 , 14 – 16 ), which was consistent with our results. Droby and colleagues conducted a prospective study in patients who experienced post-lumbar puncture and found that compared to participants who did not develop a POH, patients that developed a POH were younger ( P = 0.033) ( 17 ).…”
Section: Discussionsupporting
confidence: 93%
“…Younger age and female sex have been reported to be associated with the development of POH in various surgeries ( 8 , 9 , 11 , 14 – 16 ), which was consistent with our results. Droby and colleagues conducted a prospective study in patients who experienced post-lumbar puncture and found that compared to participants who did not develop a POH, patients that developed a POH were younger ( P = 0.033) ( 17 ).…”
Section: Discussionsupporting
confidence: 93%
“…The decision and clinical impact curves of the nomogram models also indicated remarkable predictive power and good clinical utility. Although significant predictors for POH after surgery vary considerably in different reports, female gender as an independent risk factor for POH has been widely identified in the literature (10,13,18,20,26,27), which was reconfirmed by our results. Paraskevi and colleagues reported that compared with male patients, the risk of POH increased significantly in female patients (OR =2.1, P=0.024) (13).…”
Section: Discussionsupporting
confidence: 86%
“…There have been several studies that looked at the risk factors for POH after surgical procedures in other diseases (6,13,18,19,21). However, studies conducted in patients undergoing cardiac surgery are still lacking in this field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations